A connecting hinge represses the activity of endothelial nitric oxide synthase - Haque, Mohammad Mahfuzul (National Academy of Sciences, 2007)
In mammals, endothelial nitric oxide synthase (eNOS) has the weakest activity, being one-tenth and one-sixth as active as the inducible NOS (iNOS) and the neuronal NOS (nNOS), respectively. The basis for this weak activity is unclear. We hypothesized that a hinge element that connects the FMN module in the reductase domain but is shorter and of unique composition in eNOS may be involved. To test this hypothesis, we generated an eNOS chimera that contained the nNOS hinge and two mutants that either eliminated (P728IeNOS) or incorporated (I958PnNOS) a proline residue unique to the eNOS hinge. Incorporating the nNOS hinge into eNOS increased NO synthesis activity 4-fold, to an activity two-thirds that of nNOS. It also decreased uncoupled NADPH oxidation, increased the apparent K(m)O(2) for NO synthesis, and caused a faster heme reduction. Eliminating the hinge proline had similar, but lesser, effects. Our findings reveal that the hinge is an important regulator and show that differences in its composition restrict the activity of eNOS relative to other NOS enzymes.